Fraser Syndrome: A Rare Case Report - Shrestha, Sandeep; Thani, Kamal Prasad; Keshari, Munna; Shrestha, Annie (Journal of Karnali Academy of Health Sciences, 2022)
Fraser syndrome is a rare congenital autosomal recessive condition. It is characterized by cryptophthalmos, craniofacial dysmorphism, syndactyly, laryngeal and genitourinary malformations and musculoskeletal anomalies. Here we report a case of a neonate who presented with multiple congenital abnormalities and clinical features that suggest the possibility of Fraser syndrome.